Overview of Current Situation and Trend of Offshore Wind Power Development in China - YAN Xinrong; ZHANG Ningning; MA Kuichao; WEI Chao; YANG Shuai; PAN Binbin (发电技术, 2024)
Under the carbon peak goal and carbon neutral vision, offshore wind power has made great progress in China in recent years. The current development status and future planning of offshore wind power in China were analyzed, summarizing the installed capacity of offshore wind power, new models and adopted technical routes. The paper focused on the basic type, anti-corrosion technology, and operation and maintenance technology of offshore wind power. The floating offshore wind power was the focus of basic type research. The inspection and management systems for operation and maintenance were the primary focus of research in wind power operation and maintenance technology. By analyzing the development status of offshore wind power, the main technical routes and advanced achievements of each technology were identified. Finally, based on the current status and needs of domestic technology development, the future development trends of China's offshore wind power were prospected.